L'opportunità dell'innovazione (2007)
Over the last few years the landscape debate has taken a new turn, shifting from concerns of conservation and protection towards the search for methods of intervention and regulations that consent a development of the territory compatible with the mutation of collective requirements. This is based on a recognition of the intrinsically dynamic nature of the landscape, conceived both in its matter and in its essence as a social construct. This shift has been sanctioned by the European Landscape Convention, which includes among the objectives of landscape policy the creation of new landscapes "to satisfy the aspirations of the population involved". This book focuses on the investigation of the conditions of the context that make innovation more or less appropriate. This is assessed as a design approach (and hence no distinction will be made between design action and planning action) that addresses the "rules" dictated by what already exists. The social recognition of their value defines the "degree of freedom" of the invention. At times the rule is the very object of the project, that is the intervention is demanded precisely to conserve or valorise a landscape that is considered of exceptional value (as in the case of protected landscapes). In other cases it is a question of implementing projects with different objectives, while respecting the rules of the landscape context. Frequently the landscape does not feature a single, unequivocal and legible system of rules, but a stratification that may be incomplete, fragmentary or conflicting: the project may then attempt to knit these up, and this mechanism may trigger its added value. There are also cases in which the rule is too weak to support a revival, or is "banal", in short can be considered worth "sacrificing" to the introduction of a new system of values. Taken as a whole, the essays explore cases of landscape design, from planning to the art of the garden, identifying the appropriateness of the innovation in terms of an awareness of the rules and the intentional affirmation and expression of self. The articles contained in the book were composed specifically for the International Convention on "Innovation and Rules in Landscape Design" held in Florence on 22 and 23 November 2002, organised by the Research Doctorate in Landscape Design of the University of Florence.